O podstawach teoretycznych semantycznej kategorii ablatywności w językach słowiańskich - Lachur, Czesław (Acta Polono-Ruthenica, 2008)
The basis for designation of the category of ablativeness is apresence in a language of a physical idea of translocation of an object with respect to a localizer as well as specific linguistic means which reflect the said idea. Ablativeness is a specific type of movement indicating translocation from the localizer (or its part). Such understanding of ablativeness reflects a mode of perception of specific phenomenon in reality by language users. Therefore this article discusses the very essence of semantic category of ablativeness.